Autoimmune Variant PTPN22 C1858T Is Associated With Impaired Responses to Influenza Vaccination. (30th March 2016) - Crabtree, Juliet N.; He, Wenqian; Guan, Weihua; Flage, Mark; Miller, Matthew S.; Peterson, Erik J.
Abstract: High-affinity–antibody production, T-cell activation, and interferon upregulation all contribute to protective immunity that occurs in humans following influenza immunization. Hematopoietic cell-specific PTPN22 encodes lymphoid phosphatase (Lyp), which regulates lymphocyte antigen receptor and pattern recognition receptor (PRR) signaling. A PTPN22 variant, R620W (LypW), predisposes to autoimmune and infectious diseases and confers altered signaling through antigen receptors and PRRs. We tested the hypothesis that LypW-bearing humans would have diminished immune response to trivalent influenza vaccine (TIV). LypW carriers exhibited decreased induction of influenza virus–specific CD4 + T cells expressing effector cytokines and failed to increase antibody affinity following TIV receipt. No differences between LypW carriers and noncarriers were observed in virus-specific CD8 + T-cell responses, early interferon transcriptional responses, or myeloid antigen-presenting cell costimulatory molecule upregulation. The association of LypW with defects in TIV-induced CD4 + T-cell expansion and antibody affinity maturation suggests that LypW may predispose individuals to have a diminished capacity to generate protective immunity against influenza virus.